Coaching youth rugby an essential guide for coaches, parents and teachers - Richardson, Keith (The Crowood Press Ltd, 2014)
An essential guide for all coaches, parents, and teachers of young rugby players, written by an experienced rugby coach This one-stop practical resource will give a new coach everything they need to deliver fun, dynamic, player-centered practice sessions and guidance on how to run a team. Coaches at all levels of the game will find materials and ideas aimed at helping them to formulate simple strategies to suit their level of player ability. Included are lots of practical small-team games and drills; these enable coaches to run active and fun sessions for young players, and help teach fundamental rugby skills, from passing and handling to tackling, kicking, scrum, and lineout.